A102: Acceptability and Practicality of the Paediatric Gait, Arms, Legs and Spine Examination in Detecting Musculoskeletal Abnormalities in Peruvian Children. Issue 11 (March 2014) - Abernethy, Katrina; Jandial, Sharmila; Hill, Lucy; Sánchez, Ernesto Salazar; Foster, Helen
Abstract : Background/Purpose: The paediatric Gait, Arms, Legs and Spine (pGALS) musculoskeletal examination tool (Foster & Jandial 2013) has been validated for use in school‐aged English Speaking children. pGALS detects significant joint abnormalities when performed by non specialists in paediatric rheumatology and has been shown to be practical and effective in acute paediatric practice in the UK (Goff 2010) and Malawi (Smith 2012). The aim of this study was to assess the acceptability and practicality of a Spanish translation of pGALS in an acute paediatric setting in Peru. Methods: pGALS was translated into Spanish in collaboration with the School of Modern Languages, Newcastle University. Over a two week period in summer 2013, 53 school‐aged children presenting to a teaching hospital in a large city in Peru were recruited following informed consent from parents/carers. The pGALS assessment was conducted in Spanish by a medical student (KA), a native English speaker with Spanish as a second language, who has completed standard training in pGALS at Newcastle medical school. Data collected included patient demographics, presenting complaint, final diagnosis (from case notes), and findings of the pGALS assessment. Acceptability, with regards to time taken and discomfort, was assessed using visual analogue scales (smiley faces). This study had full ethical approval. Results: Fifty‐three children were recruited (21 female, 32 male), median age 9 years old (range 4‐15 years). Many (54.3%, 33/53) were assessed in the emergency department with the remainder as inpatients. The presenting complaint and final diagnosis most commonly related to infections (73.9%, 39/53). The pGALS examination was completed in 92.5% (49/53) of children, reasons for non‐completion were limb fracture (n = 2), snakebite related pain (n = 1) and vomiting due to dengue fever (n = 1). The time taken (median 4.42 minutes, range 2.47–6.50) was acceptable to most parents (98.1%, 52/53). Most children (88.7%, 47/53) found the pGALS examination caused little or no additional discomfort. Significant findings using pGALS were found in 18/53 (34%); these related to limited limb movement due to fracture (4/18), hypermobility (4/18), plus infectious causes (5/18) and soft tissue trauma (5/18) causing pain and joint restriction in limbs, cervical spine or temporomandibular joints. The commonest findings of pGALS were abnormal gait (limp) (n = 5) and loss of foot arches (n = 4). Conclusion: The pGALS assessment was acceptable to patients and their parents, practical and detected significant musculoskeletal changes in many children. As in previous studies of pGALS in acute paediatrics, it is important to interpret the findings in the clinical context as abnormal findings may be caused by non rheumatic disease. The Spanish translation of pGALS was effective and further work is in progress to assess validity and use in similar health care settings.